Diagnostic camouflage: A case report on Latent autoimmune diabetics of adulthood. (October 2022) - Neupane, Sandhya kiran; Jaishi, Prakash Paudel; Koirala, Divyaa; Kandel, Arjun; Neupane, Prabhat Kiran
Abstract: Introduction and importance: Latent autoimmune diabetes of adulthood is an autoimmune disease sharing similarities of type 1 and type 2 diabetics. It is also known as type 1.5 diabetes in adults. It occurs mostly at the age of 30–35 years. It is usually associated with other autoimmune diseases and patients usually have normal BMI. Patients are positive for glutamic acid dehydrogenase and islets cell autoantibodies with onset in adulthood. Case: We present a case of a 42 year old female from the capital city of Nepal who presented with chief complaints of excessive thirst and increased frequency of micturition. . She also reported feeling hungry most of the time. She added having symptoms of dry mouth, fatigue and occasional dizziness. Clinical findings and investigations: Fasting and post prandial blood glucose, Hba1c, blood pH and bicarbonate, Islet cell antibodies, Glutamic Acid Decarboxylase (GAD) and urine ketones were sent for diagnosis. Intervention and outcome: The patient was started on basal bolus glargine, 14 units and rapid acting insulin, lispro 6unit each with breakfast, lunch, and dinner. Beside insulin, the patient was started on statin (10mg, rosuvastatin) and aspirin (75mg, PO). In subsequent follow-up, her HbA1c level dropped in a few months. Conclusion: There are no studies found in LADA in Nepal. Our case report tends to highlight the importance of clinical recognition of LADA and raise awareness and importance of diagnostic methods to differentiate between Type 1, Type 2 DM and LADA. Highlights: LADA is under diagnosed in many countries including Nepal. LADA is an autoimmune disease sharing a wide range of similarities of type 1 and type 2 diabetes. Patients are positive for glutamic acid dehydrogenase and islets cell autoantibodies with onset in adulthood. LADA patients required insulin therapy earlier as compared to that of Type 2 diabetes patients.